Review: Emmanuel Akyeampong, Robert H. Bates, Nathan Nunn, and James A. Robinson (eds), Africa’s Development in Historical Perspective (2014) - Frederick Cooper (Africa Spectrum, 2015)
Review of the edited volume:Emmanuel Akyeampong, Robert H. Bates, Nathan Nunn, and James A. Robinson (eds), Africa’s Development in Historical Perspective, Cambridge: Cambridge University Press, 2014, ISBN 9781107041158 (hardback), 9781107691209 (paperback), 539 pages